DNA sequence from the histidine operon control region: seven histidine codons in a row. - Barnes, W M (1978)
The DNA sequence of 250 base pairs preceding the first structural gene of the histidine operon of Salmonella typhimurium was determined by the dideoxy chain-termination method. Single-stranded DNA template was provided by an M13-histidine transducing phage constructed for the purpose by in vitro recombination. The termination site for the histidine leader RNA is identified by analogy with the trp operon leader termination sequence, and is 47 nucleotides before the start codon of the first structural gene G. Beginning 150 nucleotides before the end of the presumed leader RNA is a possible short protein-coding region with seven histidine codons in a row. It is proposed that the major mechanism of histodine operon control must involve a ribosome arrested at this run of histidine codons when histidine is limiting.